Benefits and Limitations of Macrotextured Breast Implants and Consensus Recommendations for Optimizing Their Effectiveness. (August 2014) - Maxwell, G. Patrick; Scheflan, Michael; Spear, Scott; Nava, Maurizio B.; Hedén, Per
Implant texture is an important factor influencing implant selection for breast augmentation. Natrelle Biocell implants are characterized by macrotextured shell surfaces containing irregularly arranged concavities with large open-pore diameters and depths. These properties facilitate adhesion of the implant to the surrounding tissue, thereby promoting implant immobilization. Relative to implants with other surfaces, macrotextured implants offer low rates of capsular contracture; low rates of malposition, rotation, and rippling; and high rates of patient satisfaction. However, macrotextured implants are associated with a slightly higher risk of double capsule and late seroma. The surgeon can minimize these risks with straightforward techniques that encourage tissue adhesion. This report presents experience-based recommendations to optimize the effectiveness of Biocell anatomic implants. The authors discuss the application of best practices to all aspects of the breast implantation process, from implant selection and surgical planning to operative technique and postoperative management. Level of Evidence: 3